Determinant social factors influencing obesity among Malay people - Saif Ullah, Norizan Abdul Ghani,; Saputra, Jumadil; Umair Khan, M. (Opción, 2020)
This study has explored the determinant social factors of obesity among Malay obese people. Multiple regressions analysis (stepwise method) was performed to identify and examine the most influenced factors that contribute to obesity. The analysis determined that eating habits, physical activity barriers, and feelings (low self-esteem) are dominating social factors. However, among these factors eating habits were observed as the most influencing predictor in the model. In conclusion, this pioneering study is providing baseline data of influencing factors of obesity in Malaysia, so future researches may be conducted based on the given results to reduce the obesity trend.